The evolution of flocculation reactions and gamma globulins at the Peruvian wart - Manrique, Vitaliano (1956)
Bartonellosis, or Carrión Peruvian wart disease, are characterized in the acute state, severe anemia and symptoms resulting from this and primitive or secondary infection status that sometimes, it is much more serious. In the chronic state of anemia is moderate or slight and often unnoticed and appears verrucous outbreak is repeated more or less marked cycles or reduction of organic resistance, and its appearance is made with painful manifestations.